An Ultrafast and Stable Li‐Metal Battery Cycled at −40 °C. (25th December 2022) - Cheng, Liwei; Wang, Yingyu; Yang, Jie; Tang, Mengyao; Zhang, Chenguang; Zhu, Qiaonan; Wang, Sicong; Li, Yuting; Hu, Pengfei; Wang, Hua
Abstract: Li‐metal battery (LMB) suffers from the unexpected Li dendrite growth and unstable solid‐electrolyte interphase (SEI), especially in the extreme conditions, such as high rates and low temperatures (LT). Herein, a high‐rate and stable LT LMB is realized by regulating electrolyte chemistry. A weak Li + ‐solvating solvent 2‐methyltetrahydrofuran is used as electrolyte solvent to mitigate the kinetic barrier for Li + de‐solvation. Moreover, a co‐solvent tetrahydrofuran with a high donor number is incorporated to improve the LT solubility of Li salts, achieving an improved ionic conductivity while maintaining the weak Li + ‐solvation effect. Furthermore, abundant FSI ‐ anions in contact‐ion pairs are presented, facilitating the formation of a stable LiF‐enriched SEI. Consequently, the Li||Li battery can be operated at 10 mA cm ‐2 with a small polarization of 154 mV at −40 °C. Meanwhile, an outstanding cumulative cycling capacity of 4000 mAh cm ‐2 at 8.0 mA cm ‐2 is achieved, reaching a record high level in LT alkali metal symmetric batteries. Also, rechargeable high‐rate and stable full batteries are achieved at −40 °C. This work demonstrates the superiority of electrolyte chemistry for synergistic regulation of both ion transfer kinetics and SEI toward ultrafast and stable rechargeable LMBs at LT. Abstract : A high‐rate and stable low temperature Li metal battery is achieved through adjusting the solvation configuration of the electrolyte. Due to the weak Li + ‐solvation effect and stable LiF‐enriched solid‐electrolyte interphase, both Li metal based symmetric battery and full battery exhibit superior rate performance and excellent cyclability at low temperature.